Lietuvos Didžiosios Kunigaikštystės susidarymo problemos: Baltarusių istoriografijos apžvalga - Nasevich, Viachaslau (Lietuvos istorijos studijos, 2008)
In the early 1920s, the historians who identified themselves as Belarusians (U. Ignatouski, M. Dounar-Zapolski) formulated their position regarding the formation of the Grand Duchy of Lithuania. They accentuated the peaceful involvement of the Belarusian lands into the new state triggered by Lithuanians and claimed its mutual essence as the Lithuanian-Belarusian state. A new accent was brought by M. Shkialionak, who contended in the 1930s that the real triggers of the Grand Duchy of Lithuania formation were the Belarusians, and the state was predominantly Belarusian. The two alternative views coexist in the Belarusian historiography hitherto.